Levels of Prothrombin Fragment F1+2 in Patients with Hyperhomocysteinemia and a History of Venous Thromboembolism - Kyrle, Paul A; Stümpflen, Andreas; Hirschl, Mirko; Bialonczyk, Christine; Herkner, Kurt; Speiser, Wolfgang; Weltermann, Ansgar; Kaider, Alexandra; Pabinger, Ingrid; Lechner, Klaus; Eichinger, Sabine (Thrombosis and Haemostasis, 1997)
Increased thrombin generation occurs in many individuals with inherited defects in the antithrombin or protein C anticoagulant pathways and is also seen in patients with thrombosis without a defined clotting abnormality. Hyperhomocysteinemia (H-HC) is an important risk factor of venous thromboembolism (VTE). We prospectively followed 48 patients with H-HC (median age 62 years, range 26-83; 18 males) and 183 patients (median age 50 years, range 18-85; 83 males) without H-HC for a period of up to one year. Prothrombin fragment Fl+2 (Fl+2) was determined in the patient’s plasma as a measure of thrombin generation during and at several time points after discontinuation of secondary thromboprophylaxis with oral anticoagulants. While on anticoagulants, patients with H-HC had significantly higher Fl+2 levels than patients without H-HC (mean 0.52 ± 0.49 nmol/1, median 0.4, range 0.2-2.8, versus 0.36 ± 0.2 nmol/1, median 0.3, range 0.1-2.1; p = 0.02). Three weeks and 3,6,9 and 12 months after discontinuation of oral anticoagulants, up to 20% of the patients with H-HC and 5 to 6% without H-HC had higher Fl+2 levels than a corresponding age- and sex-matched control group. 16% of the patients with H-HC and 4% of the patients without H-HC had either Fl+2 levels above the upper limit of normal controls at least at 2 occasions or (an) elevated Fl+2 level(s) followed by recurrent VTE. No statistical significant difference in the Fl+2 levels was seen between patients with and without H-HC. We conclude that a permanent hemostatic system activation is detectable in a proportion of patients with H-HC after discontinuation of oral anticoagulant therapy following VTE. Furthermore, secondary thromboprophylaxis with conventional doses of oral anticoagulants may not be sufficient to suppress hemostatic system activation in patients with H-HC.